Effect of Water Stress on Yield and Seed Quality of Coriander (Coriandrum sativum L.) - Thakur, Priyanka; Thakur, Anju (International Journal of Bio-resource and Stress Management, 2018)
Coriander (Coriandrum sativum L.) is an annual herbaceous plant commonly known as Cilantro or Dhania, belonging to family Apiaceae (Umbelliferae), it is a powerful herb with many health benefits.It is a dual purpose crop grown for its aromatic leaves and cremocarpic seeds, which are extensively used as a spice and food flavouring agent. Plant growth is seriously affected by abiotic stresses and drought is one of the most important limiting factors. Drought stress during earlyreproductive growth stage usually reduces the seed yield and seed quality. To assess the effect of drought stress on seed yield and seed quality of coriander, the experiment was conducted in green house in plastic pots at Dr. Y.S. Parmar University of Horticulture and Forestry, Nauni, Solan (H.P.) during the Rabi season of 2012–13. Coriander cv. Solan Selection was used as a test crop. There were four treatments of Water stress i.e. T1-Control,T2-25%, T3-50%, and T4-75% Water deficit imposed at flower forming phase for 15 days.The treatments were arranged in a design CRD (Completely Randomized Design) with fourreplications. Data were recorded and results indicated the significant reduction in plant height stress index, dry matter index, biological yield, number of seeds per plant, harvest index (HI) and yield stability ratio and also observed per cent reduction in 1000- seed weight ,seed moisture content and germination percentage. On other hand there where per cent increase in solute leakage, mean germination time.